Experimental indications of gardeners’ anecdotes that snails interfere with invasive slugs - Dörler, Daniel; Dorn, Verena; Widhalm, Theresia; Horacek, Micha; Heigl, Florian; Euteneuer, Pia; Leisch, Friedrich; Frank, Thomas; Zaller, Johann G. (PeerJ, 2021)
The invasive Spanish slug (Arion vulgaris) is an important pest species in agriculture and horticulture in Europe. In the last decades it has spread across the continent where it outcompetes native slug and snail species, thus posing a threat for biodiversity. A popular anecdote suggests to promote Roman snails (Helix pomatia) in gardens because they are able to control A. vulgaris. We examined a potential interrelationship between these two species using a mesocosm experiment with lettuce plants. 13C-15N stable isotope labelling of lettuce allowed us to investigate interactions between Helix and Arion on weight gain/loss and herbivory. Additionally, we wanted to know whether different watering regimes (daily vs. every 3rd day watering of weekly amount) and earthworms alter these interactions. Egg predation of Helix on Arion eggs was further tested in a food-choice experiment. Arion showed a five times higher herbivory per body mass than Helix in a single-species setting. However, in mesocosms containing both species percentage of herbivory per body mass was significantly lower than in Arion-only mesocosms, especially when watered every three days. Overall isotope uptake via eaten lettuce was unaffected by the presence of the other species. Only very little predation (three out of 200 eggs) of Helix on Arion eggs was observed. Our results provide no evidence for a clear dismissal or confirmation of the popular gardener’s anecdote that Helix snails have a negative effect on Arion abundance or herbivory.
Keywords: Invasive species; Invasion biology; Aboveground-belowground-interactions; Snail-slug-interaction; Stable isotope tracing